Change management in public sector / Wan Narita Mustapha … [et al.] - Mustapha, Wan Narita; Hamidun, Noor Hamimah; Amer, Noryanne; Hashim, Rugayah (Universiti Teknologi MARA, Shah Alam, 2004)
Change is the engine which drives success for an individual or even an entire industry. This statement is supported by Burnes (2004) that change is an important factor for an organization’s life both at a strategic and operational level. For the public sector, during unwarranted periods, for example during an economic downturn, change is crucial to sustain progress. By its very nature, progress involves change, via technological advancement, new concepts or simply a refocusing of efforts. Managers are the individuals designated to lead the employees to betterment by their actions and behavior they can create an atmosphere which is either stifling, encouraging the maintenance of status quo or vibrant with enthusiasm for change and improvement. In response to that, Burnes, 2004; Riley and Clarkson, 2001 further discussed that it is necessary for organization under change process to effectively respond to and closely related to organizational strategy or vice versa. Senior (2002) explained that in order to ensure realization of change process, government and public sectors have to strive and acquire good managerial skills. Successful and effective management is important to ensure an organization survival and success in today’s competitive business environment.